The Impact of TikTok Live Streaming Marketing Strategies on Consumer Purchase Decisions: A Study of the Tala Outfit Brand - Phyta Rahima; Arwin Yafi Rahmatullah; Susilo Talidobel (Valid: Jurnal Ilmiah, 2026)
This study aims to determine and analyze the influence of Tala Outfit’s live streaming digital marketing strategy on TikTok toward consumer purchasing decisions. The study employed a quantitative research method using descriptive and causal approaches. The descriptive approach was used to explain the implementation of Tala Outfit’s live streaming strategy, including host performance, discount promotions, audience interaction, and sales improvement, while the causal approach was applied to analyze the influence of the live streaming strategy on consumer purchasing decisions. The data used in this study consisted of primary and secondary data. Primary data were collected through the distribution of online questionnaires to consumers, whereas secondary data were obtained from Tala Outfit’s internal company records, including time series data on live streaming performance and monthly sales data for the period of September 2024 to October 2025. The results showed that Tala Outfit’s live streaming strategy on TikTok, particularly through competent host performance and attractive discount promotions, successfully increased audience interaction and gross revenue by 627.85%. Therefore, the findings indicate that live streaming is an effective digital marketing strategy for increasing audience traffic and influencing consumer purchasing interest.